2012
DOI: 10.4137/cment.s8610
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and Alcohol Ingestion as Risk Factors for Laryngeal Squamous Cell Carcinoma at Kenyatta National Hospital, Kenya

Abstract: Laryngeal squamous cell carcinoma (SCC) is strongly linked to cigarette smoking. It is estimated to account for more than 70% of laryngeal SCCs and up to 89% in combination with alcohol. We wished to determine the prevalence of cigarette smoking and alcohol ingestion among patients with laryngeal squamous cell carcinoma and estimate risk attributed to cigarette smoking and alcohol ingestion. Fifty experimental group patients and fifty controls were recruited of matching age, sex and region of residence. Histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 29 publications
0
20
0
2
Order By: Relevance
“…Laryngeal cancer is the highest incidence of head and neck cancer and probably accounts for 1%~5% cancer incidence worldwide . Smoking and alcohol are considered as common major risk factors for laryngeal cancer . Moreover, some researchers have found that people with a family history of cancer are also susceptible to laryngeal cancer, which implicates that genetic factors serve an important role in the occurrence and progression of laryngeal cancer .…”
Section: Introductionmentioning
confidence: 99%
“…Laryngeal cancer is the highest incidence of head and neck cancer and probably accounts for 1%~5% cancer incidence worldwide . Smoking and alcohol are considered as common major risk factors for laryngeal cancer . Moreover, some researchers have found that people with a family history of cancer are also susceptible to laryngeal cancer, which implicates that genetic factors serve an important role in the occurrence and progression of laryngeal cancer .…”
Section: Introductionmentioning
confidence: 99%
“…Cancer of the larynx accounts for ~1.2% of new malignancies worldwide every year, with an incidence of ~151,000 cases per year, ~95% of these tumors have squamous cell carcinoma as the primary histological type (1,2). It has been reported that this neoplasia is strongly linked to cigarette smoking, alcohol ingestion and human papillomavirus infection (3)(4)(5). Treatment options in laryngeal carcinoma comprise surgery, radiotherapy, chemotherapy or a combination therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The risk imparted by both factors has been shown to be synergistic thus increasing the risk of squamous cell carcinoma by many fold [4, 9, 10]. However, alcohol as an independent risk factor for laryngeal cancer remains controversial [10].…”
Section: Introductionmentioning
confidence: 99%